“WHEN HE ARRIVED IN ROME, HE EAGERLY SEARCHED FOR ME!” (2 TIM 1,17). FRIENDS, FOES, AND NETWORKS IN 2 TIMOTHY - ZAMFIR, Korinna (Studia Universitatis Babeș-Bolyai Theologia Catholica Latina, 2022)
The antagonistic discourse of 2 Timothy divides the community into two camps: the truthful believers and the heterodox opponents of Paul. Emphasis on cohesion, on the strong links between Paul and friends and delineation from those depicted as dangerous outsiders strengthen group identity. However, perspectives from network theory show that Christ-believers did not belong to impermeable camps. Proximity, multiplex social relations (shared family, neighbourhood, or occupational ties, worship, and commensality) created opportunities for communication and exchange. Weak ties bridged the gap between various clusters, shaping networks akin to small worlds, allowing for interactions across partisan lines and for more inclusive forms of identity.